Visualizing Forestry Operators’ Work - ForReel: Supporting harvester operators’ professional identity in an increasingly automated industry - Wang, Chia-An; Einarsdóttir, Eva Sif (My University, 2026)
The forestry industry in Sweden is highly automated, and this trend is accelerating day by day. While this technological shift increases efficiency, it introduces the risk of operator deskilling, a diminished autonomy with subsequent demotivation and disengagement. This thesis explores how increasing automation impacts the professional identity of harvester operators and investigates how Interaction Design can be used to support it. In collaboration with the User Experience department at Volvo Penta, this challenge is addressed by applying a Research-through-Design method to identify the core elements that construct an operator’s professional identity. The double-diamond design process resulted in a highlight reel system–ForReel, intended to preserve the operators’ professional identity by making their real work visible both for self-reflection and to others for more social recognition. This design concept utilizes multimodal data collection, fusing mechanical data with biometric sensors and manual inputs, to capture moments of exceptional operational skill, for example, difficult-terrain navigation, deliberate overrides of algorithmic suggestions, and flow states. The concept was first evaluated through an online survey with a storyboard, and then field tests were conducted using a Wizard of Oz simulation. The key feature of a highlight reel received positive feedback from participating harvester operators. The findings suggest that Interaction Design interventions can potentially sustain harvester operators’ professional identity by translating abstract production metrics into clear, shareable proof of their invisible expertise.
Keywords: Forestry harvester operators, Automation, Professional identity, Human machine interaction, User-centered design